Improving lupus care index documentation in patients with childhood-onset systemic lupus erythematosus - Barbar-Smiley, Fatima A.; Yildirim-Toruner, Cagri; Akoghlanian, Shoghik; AlAhmed, Ohoud; Ardoin, Stacy P.; Leone, Ashlee; Oberle, Edward; Sivaraman, Vidya (Frontiers in Pediatrics, 2024)
Introduction Childhood-onset systemic lupus erythematosus (c-SLE) presents unique challenges due to increased risk for severe morbidity and mortality compared to adult-onset SLE. Effective disease management relies on accurate disease assessment and documentation. Our project aimed to improve the documentation of the Lupus Care Index (LCI), a disease assessment bundle, by implementing a quality improvement (QI) initiative. Methods A QI project was conducted at Nationwide Children's Hospital (NCH), targeting patients with c-SLE. The LCI, comprising the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI-2k) Physician Global Assessment (PGA) and patient-reported pain score, was introduced to capture comprehensive disease assessment. Interventions included provider education, standardization of documentation procedures, and electronic health record (EHR) modifications. Automated reports tracked documentation rates, and Pareto charts identified areas for targeted interventions. Results Baseline analysis revealed incomplete documentation of LCI components in only one-third of c-SLE patients. Following interventions, documentation rates improved from 38% to 90%, with sustained improvement over at least a year. Discussion Enhancing documentation of LCI in patients with c-SLE is crucial for optimizing disease management. Our quality improvement initiative demonstrated the feasibility of improving documentation practices through targeted interventions and system modifications. Future research should explore the impact of comprehensive documentation on clinical outcomes in pediatric lupus patients. Improving documentation of LCI in patients with c-SLE is essential for optimizing care delivery and clinical outcomes; our QI initiative highlights the effectiveness of systemic interventions in enhancing documentation practices and underscores the importance of continued efforts to improve pediatric lupus care.